2022
DOI: 10.1039/d1ob02143e
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free three-component cyanoalkylation of quinoxalin-2(1H)-ones with vinylarenes and azobis(alkylcarbonitrile)s

Abstract: We have unveiled an efficient synthesis of cyanoalkylated quinoxalin-2(1H)-ones via a three-component radical cascade reaction of quinoxalin-2(1H)-ones with vinylarenes and azobis(alkylcarbonitrile)s. K2S2O8 takes part in the reaction as a sole...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 125 publications
0
13
0
Order By: Relevance
“…In 2022, Bhuyan and co-workers reported a multiple component radical cascade reaction initiated by AIBN. 25 In this example, no transition-metal catalyst was used, and K 2 S 2 O 8 was applied as oxidant. This approach represents a green cyanation methodology with no highly toxic nitrile source used.…”
Section: Radical Addition Of Alkenes and Alkynes Using Aibn As Cyanoa...mentioning
confidence: 99%
“…In 2022, Bhuyan and co-workers reported a multiple component radical cascade reaction initiated by AIBN. 25 In this example, no transition-metal catalyst was used, and K 2 S 2 O 8 was applied as oxidant. This approach represents a green cyanation methodology with no highly toxic nitrile source used.…”
Section: Radical Addition Of Alkenes and Alkynes Using Aibn As Cyanoa...mentioning
confidence: 99%
“…[64] Recently, radical difunctionalization of styrenes has been a topic of keen interest in organic synthesis as it leads to the formation of complex organic molecules in a single step with broad functional group tolerance. [65] Very recently, several research groups around the world have reported the threecomponent cascade C3 alkylation of quinoxalin-2(1H)-ones using olefins and styrenes as intermediary radical acceptors and different radical precursors such as perfluoroalkyl iodides, [66] TMSN 3 , [67] CF 3 SO 2 Na, [68] sulfinic acid, [69] DMSO, [70] and AIBN [71] to produce diverse 3-alkylated quinoxalin-2(1H)-one derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, we reported the cross-dehydrogenative coupling reaction of 4-hydroxycoumarins and 4-hydroxy-6-methyl-2pyrone with quinoxalin-2(1H)-ones. [72] Again, we have just published a three-component radical cascade reaction of quinoxalin-2(1H)-ones with vinylarenes and azobis(alkylcarbonitrile)s. [71] Based on the above two reports, we hypothesized the three-component radical cascade reaction of 4-hydroxycoumarins and 4-hydroxy-6-methyl-2-pyrone with quinoxalin-2(1H)-ones by using vinylarenes as intermediary radical acceptor might be feasible. In continuation of our research program (Scheme 1, [15,71,72] we, herein, wish to report a three-component reaction of quinoxalin-2(1H)-ones with 4hydroxycoumarins/4-hydroxy-6-methyl-2-pyrone and vinylarenes for the synthesis of 3-alkylated quinoxalin-2(1H)-ones using K 2 S 2 O 8 as the sole oxidant.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations